Designing Justice: The Influence of Constitutional Review Mechanisms on Minority Rights Protection in Democracies - Siswadhi, Reyhan Mahardika; Aprilliani (Indonesian Scientific Publication, 2025)
This study examines the empirical relationship between constitutional review models and the protection of minority rights in democratic states. While international human rights instruments set normative standards, domestic institutional designs determine how these norms are implemented and enforced. The research evaluates whether countries with stronger constitutional review systems—particularly those featuring centralized courts, abstract review powers, and individual constitutional complaint mechanisms—are more effective in protecting minority rights. Using a cross-national panel dataset covering 2000–2024, the analysis integrates data from the Comparative Constitutions Project, World Justice Project, V-Dem, and Minority Rights Group. Key dependent variables include the WJP Fundamental Rights Index and V-Dem’s Equality before the Law and Liberty Index. Independent variables capture review typologies and structural features, while controls address regime type, economic development, and minority risk context. Analytical methods—OLS, GLS, event studies, and propensity score matching—are employed to test causal robustness. Results show that centralized constitutional review and individual access mechanisms significantly correlate with higher levels of minority rights protection. Event-study analyses demonstrate post-reform improvements in rights indices, and matched comparisons confirm positive treatment effects. These findings underscore how institutional design influences human rights enforcement. The study contributes to comparative constitutional law and political science by empirically linking judicial structure to rights outcomes. It concludes that robust constitutional review mechanisms, supported by democratic governance and institutional integrity, are critical to translating normative commitments into tangible protections for minority groups.